THE USE OF ALTERNATIVE METHODS IN REDUCING MENOPAUSAL COMPLAINTS IN TURKEY - Ege, Emel; Kal, Halime Esra; AltuntuÄŸ, Kamile (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Millions of women experience menopause every year, therefore the aim of this study is to determine the rates of application of alternative methods applied by women in order to reduce their complaints caused by menopause and alternative application methods. Materials and Methods: This study was carried out on 246 women in their menopausal period. The data was obtained by the researcher through face to face interviews during the home visits. During the collection of data, a questionnaire form by the researcher that was developed in accordance with the literature information was applied. Results: 37.4% of women were determined to use alternative methods to reduce their menopausal symptoms. In the consequence of statistical analysis, a significant relation was found between the menopausal complaints such as hot flashes, night sweats and sleeping problem and the use of alternative methods in order to reduce their menopausal complaints (p<0.05).Conclusion: It was determined that the women at their menopausal ages experienced vasomotor complaints and sleeping problems and they used alternative methods to reduce those problems.